2006
DOI: 10.1002/hipo.20230
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of NR2A and NR2B NMDA subunits to bidirectional synaptic plasticity in the hippocampus in vivo

Abstract: It has recently been proposed that activation of the NR2A subunit results in Long-term potentiation (LTP) induction, whereas activation of the NR2B subunit results in long-term depression (LTD) induction. The present study undertakes to replicate these findings in vivo to determine if a role for specific subunits in synaptic plasticity can be shown in the intact brain. Field recordings were made from the CA1 subfield of the hippocampus using Schaffer collateral stimulation in anesthetized male Sprague-Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 33 publications
10
125
0
Order By: Relevance
“…Of particular relevance to the present argument is the fact that NMDA NR2B receptor activation is required for the induction of LTD in vitro under some circumstances Liu et al, 2004;Woo et al, 2005;Izumi et al, 2006; but see Hendricson et al, 2002;Morishita et al, 2007) and for NMDA-induced AMPA receptor endocytosis in cultured neurons (Kim et al, 2001;Tigaret et al, 2006). Indeed, recent studies have demonstrated that systemic administration of Ro 25-6981 at the same dose used in the present study blocked selectively the induction of LTD while having no effect on LTP in the hippocampus in vivo (Fox et al, 2006;Wong et al, 2007). The Tat-GluR2 3Y peptide used in these experiments has also been shown to block the expression of LTD specifically through the blockade of regulated AMPA receptor endocytosis (Ahmadian et al, 2004;Brebner et al, 2005;Fox et al, 2007).…”
Section: Manipulations That Disrupt Ltd Formation Disrupt Fear Extincmentioning
confidence: 52%
See 3 more Smart Citations
“…Of particular relevance to the present argument is the fact that NMDA NR2B receptor activation is required for the induction of LTD in vitro under some circumstances Liu et al, 2004;Woo et al, 2005;Izumi et al, 2006; but see Hendricson et al, 2002;Morishita et al, 2007) and for NMDA-induced AMPA receptor endocytosis in cultured neurons (Kim et al, 2001;Tigaret et al, 2006). Indeed, recent studies have demonstrated that systemic administration of Ro 25-6981 at the same dose used in the present study blocked selectively the induction of LTD while having no effect on LTP in the hippocampus in vivo (Fox et al, 2006;Wong et al, 2007). The Tat-GluR2 3Y peptide used in these experiments has also been shown to block the expression of LTD specifically through the blockade of regulated AMPA receptor endocytosis (Ahmadian et al, 2004;Brebner et al, 2005;Fox et al, 2007).…”
Section: Manipulations That Disrupt Ltd Formation Disrupt Fear Extincmentioning
confidence: 52%
“…Nevertheless, the studies discussed above strongly suggest that the lateral nuclei of the amygdala may be an important neuroanatomical locus where blockade of AMPA receptor endocytosis or NMDA NR2B receptors would affect this form of learning. However, it is equally plausible that these effects may be due to alterations in synaptic mechanisms in the hippocampus, given that (1) both Tat-GluR2 3Y and Ro 25-6981 disrupt LTD formation in the hippocampus (Fox et al, 2006(Fox et al, , 2007Duffy et al, 2007) and (2) inactivation of this region causes a similar impairment in extinction learning (Corcoran et al, 2005). The effects of local administration of these drugs in the hippocampus and amygdala on fear extinction are the topic of current investigation in our laboratory.…”
Section: Manipulations That Disrupt Ltd Formation Disrupt Fear Extincmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the GluN2A preferential antagonist NVP-AAM077 (NVP) (19) and the GluN2B-specific antagonist Ro25-6981 (Ro) (20) selectively inhibit LTP and LTD, respectively, in anesthetized rats (18,21). If such GluN2 subunitselective requirements for LTP and LTD can be shown in freely moving animals, these subunit-preferential antagonists may be useful in delineating the roles of LTP and LTD in spatial memory.…”
mentioning
confidence: 99%